The Social Aspects and Public Acceptance of Biomass Giving the Example of a Hungarian Region - Zoltán Bujdosó; Csaba Patkós; Tibor Kovács; Zsolt Radics; Zoltán Baros (Center of Biomass & Renewable Energy, Diponegoro University, 2012)
Biomass energy sources are the most promising, and most heavily subsidized renewable energy sources. The future of biomass energy in the global energy system depends on on many major factors, among others on the attitude of society to the biomass energy and the renewable energy resources. The purpose of the paper is to analyze the opportunities of utilization of biomass energy sources giving example of a Hungarian study area furthermore to study the public acceptance of renewable energy sources in a certain region. The study aims to explore the general knowledge, innovative attitude, acceptance and willingness of application as well as the estimation of the benefits of the use of RES within the inhabitants. Data collection has carried out by primary (questionnaire survey) and secondary ways in order to gain deep information from the target group (local people). The conclusion we can drawn from the analysis is that society take the biomass energy into consideration and its importance and responsibility is increasing. As far as the consciousness is concerned, the knowledge and the environmental friendly approach of inhabitants are also sufficient.